The pyocin regulator PrtR regulates virulence expression of Pseudomonas aeruginosa by modulation of Gac/Rsm system and c-di-GMP signaling pathway - Jiao, Hongying (2021)
In Pseudomonas aeruginosa, the second messenger cyclic-di-GMP and Gac/Rsm signaling pathways are associated with the transition from acute to chronic infection. Therefore, identification of the molecular mechanisms that govern lifestyle choice in bacteria is very important. Here, we identified a novel cyclic-di-GMP modulator, PrtR, which was shown to repress pyocin production by inhibition of PrtN and activate the type III secretion system (T3SS) through PtrB. Compared to a wild-type strain or a prtN mutant, the prtR prtN double mutant exhibited a wrinkly colony and hyperbiofilm phenotype, as well as an increase in intracellular c-di-GMP levels. Interestingly, a diguanylate cyclase (DGC) gene, siaD, was repressed by PrtR. Further experiments revealed that PrtR directly interacts with SiaD and facilitates the accumulation of c-di-GMP in cells. We also demonstrated that PrtR regulates the activity of the Gac/Rsm system, thus affecting expression of the T3SS and type VI secretion system (T6SS) and the formation of biofilm. Taken together, the present findings indicate that PrtR, as a c-di-GMP modulator, plays key roles in the adaptation to opportunistic infection of P. aeruginosa Additionally, this study revealed a novel mechanism for PrtR-mediated regulation of the lifestyle transition via the Gac/Rsm and c-di-GMP signaling networks.